EFISIENSI PAKAN DAN KUALITAS KARKAS BABI YANG MENDAPAT SUPLEMENTASI LARUTAN DAUN KELOR (Moringa oleifera Lam) DALAM “LIQUID FEEDING” (Feed eficiency and pigs carcass quality wich gets supplementation of moringa oleifera solution in liquid feeding) - Ni Nengah Suryani; I Made S. Aryanta; Tagu Dodu (Universitas Nusa Cendana, 2021)
The study aimed at evaluating the effect supplementation of moringa (Moringa oleifera. L) leaves solution into liquid feeding on feed efficiency and carcass quality in landrace crossbred growing-finishing pig. There were 12 barrows with 18 – 45 (average 29.17) kg, CV 24,17% initial body weight used in the study. Trial method using block design 4 treaments with 3 replicates pocedures were applied in the study. The 4 treatment diets offered in the trial were: T0 = basal diet (control) T1 = basal diet + Moringa leaves colution 5%; T2 = basal diet + Moringa solution 10%; and T3 = basal diet + Moringa solution 15%. Variables evaluiated in the study were: Feed efficiency, carcass quality (carcass weight, carcass percentage, loin eye area and bact fat). Results this study shows the treatment of moringa leaf solution supplementation markedly into liquid feeding is not significant (P>0.05) increased on feed efficiency, carcass weight and loin eye area but significant increased (P>0.05) on carcass percentage and reduced back fat thickness. The conclusion: the treatment of moringa leaf solution has the tendency to increase feed efficiency and can improve the quality of the carcass by increasing the loin eye area and decreasing the thickness of back fat. It was concluded that moringa leaf supplementation in liquid feeding > 10% of the feed can improve carcass quality.